Analisis Dampak Pelaksanaan Kegiatan Lomba Berbasis Islami 1 Muharram dalam Membangun Generasi Berakhlak Mulia - Ridho Pangestu; Ade Elvira; Deli Pemri; Ike Nurulia Meylani; Ani Sartika (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This study aims to identify and analyze key issues related to the celebration of 1 Muharram, such as its spiritual and social significance, as well as its contribution to the solidarity of the Muslim community. The method used is a Descriptive Research. The results of the study show that 1 Muharram has a deep meaning as a day of reflection and respect for the migration of the Prophet Muhammad from Mecca to Medina, and is used as a momentum to strengthen social solidarity and spiritual commitment. The issues found include challenges in maintaining religious values in the midst of modernization, as well as the role of 1 Muharram in strengthening relations between religious communities. This research emphasizes the importance of a deep understanding of the social and spiritual role of the 1st Muharram celebration in Muslim communities.